A diquinone–imidazole ensemble for selective colorimetric sensing of cyanide in aqueous medium via anion induced NIR absorption. Issue 30 (8th March 2016) - Jayasudha, Palanisamy; Manivannan, Ramalingam; Elango, Kuppanagounder P.
Abstract : The receptor selectively and sensitively senses cyanide ions in aqueous solution with a striking colour change via anion induced NIR absorption (913 nm). Abstract : A diquinone–imidazole ensemble (R ) is rationally designed, synthesized and employed as a selective and sensitive colorimetric sensor for cyanide ions in DMSO : H2 O (1 : 4 v/v). 1 H NMR titration indicates that the mechanism of sensing involves the formation of a H-bond betweenCN − and imidazole N–H. As rationalized, theR –CN − complex exhibited intense NIR-absorption (913 nm; log  ε 4.3) with a 428 nm red-shift from the absorbance maximum of freeR . DFT calculations indicate that theR –CN − complex is perfectly planar with a HOMO–LUMO energy gap of 0.9826 eV which is optimal for NIR-absorption.